2005
DOI: 10.1111/j.1745-3992.2005.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Grade‐Level Invariance of a Theoretical Causal Structure Predicting Reading Comprehension With Vocabulary and Oral Reading Fluency

Abstract: This research investigates the relative importance of vocabulary and oral reading fluency as measurement dimensions of reading comprehension as the student passes from elementary to high school. Invariance of this model over grades 4 through 8 is tested using two independent student samples reading grade‐level appropriate passages. Results from structural equation modeling indicate that the model is not invariant across grade levels. Vocabulary knowledge is a significant and constant predictor of overall readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
102
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 24 publications
(26 reference statements)
10
102
0
6
Order By: Relevance
“…In effect, reading the words (reading accuracy) creates the message to which the reader applies comprehension. Tests of reading for older readers, including state, national, and international tests (MYCEETYA 2007;OECD 2002OECD , 2004OECD , 2007OECD , 2008OECD , 2009Yovanoff et al 2005), measure reading comprehension of authentic, or lifelike, reading tasks. In this paper, this reading comprehension of older readers using authentic reading tasks will be termed Authentic Reading.…”
Section: Early and Sophisticated Literacymentioning
confidence: 99%
“…In effect, reading the words (reading accuracy) creates the message to which the reader applies comprehension. Tests of reading for older readers, including state, national, and international tests (MYCEETYA 2007;OECD 2002OECD , 2004OECD , 2007OECD , 2008OECD , 2009Yovanoff et al 2005), measure reading comprehension of authentic, or lifelike, reading tasks. In this paper, this reading comprehension of older readers using authentic reading tasks will be termed Authentic Reading.…”
Section: Early and Sophisticated Literacymentioning
confidence: 99%
“…Наиме, лексичка димензија нема само кључну улогу у развоју језика, већ у знатној мери утиче на способност читања, али и на целокупан школски успех (Baumann, Kame'enui & Ash, 2003;Chall et al, 1990). Чак постоје мишљења да (не)препознавање значења речи може представљати ограничавајући фактор за способност читања (Cain et al, 2004;Yopp et al, 2009;Yovanoff et al, 2005). На повезаност између лексичко-семантичког развоја и способности читања указује и Лониган, наглашавајући да је за вештину читања најзначајније разумевање значења садржаја којим ученици треба да овладају, што се јасно одражава на све школске домене, а не само на наставу матерњег језика (Lonigan, 2007).…”
unclassified
“…This, however, is not the case for students with low level reading-accuracy skills. For them, the relationship of reading accuracy to reading comprehension, independent reading, and success in literacy remains strong and unequivocal Yovanoff et al, 2005). At all ages, reading accuracy is a gateway skill separating those students who succeed in literacy, from those who struggle (Catone & Brady, 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…In their study of students from Grades 4-8, Yovanoff et al (2005) reported high standard deviations for each grade's reading-accuracy mean, and a negligible change in standard deviation between grade levels. This high variability of scores suggests a wide spread of scores from high reading achievers to weak readers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation